Particle Size Effects of TiO2 Layers on the Solar Efficiency of Dye-Sensitized Solar Cells. (16th May 2013) - Jeng, Ming-Jer; Wung, Yi-Lun; Chang, Liann-Be; Chow, Lee
Abstract : Large particle sizes having a strong light scattering lead to a significantly decreased surface area and small particle sizes having large surface area lack light-scattering effect. How to combine large and small particle sizes together is an interesting work for achieving higher solar efficiency. In this work, we investigate the solar performance influence of the dye-sensitized solar cells (DSSCs) by the multiple titanium oxide (TiO2 ) layers with different particle sizes. It was found that the optimal TiO2 thickness depends on the particle sizes of TiO2 layers for achieving the maximum efficiency. The solar efficiency of DSSCs prepared by triple TiO2 layers with different particle sizes is higher than that by double TiO2 layers for the same TiO2 thickness. The choice of particle size in the bottom layer is more important than that in the top layer for achieving higher solar efficiency. The choice of the particle sizes in the middle layer depends on the particle sizes in the bottom and top layers. The mixing of the particle sizes in the middle layer is a good choice for achieving higher solar efficiency.